Peran Tindakan Strategi dan Pengorganisasian Pada Private Bisnis dan BUMN Untuk Meraih Hasil Bisnis - Prihatin Tiyanto PH (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
The modern context, firms have to combine sets of scarce resources, competencies and customers. Demanding customers and competent employees enable firms to deliver more services, a higher degree of customization, and more co-specialized interaction between supplier and customers. Mayor managerial challenges results, as neither customers nor knowledge workers accept standardized solutions. Yet there are still possibilities for improved value creation through processes of strategizing and organizingKeywords: knowledge intensive firms, professional forms, organizational complexity, strategizing organizing.